पूर्वी आ पछिमी सोचके मिलन - Kattari, Prakash; Shaha Mitra, Sanjaya (Academic Journal of Simara, 2026)
In this comparative assessment from an Eastern philosophical lens, Anjay Mishra, D.Litt., Nepal’s preeminent scientist in management, offers a profound intellectual engagement with A Reference Book on Comparative Assessment from the Eastern Approach, transcending conventional Western critiques. Previously reviewed in British English, American English, and Nepali, the work now finds vibrant expression in Bajika—a vital Indo-Aryan language of the Madhesh region—revitalizing its cultural resonance and advocating for linguistic preservation amid globalization. Mishra deftly juxtaposes Eastern paradigms of holistic governance and ethical stewardship against the book’s managerial frameworks, illuminating pathways for sustainable public administration in South Asian contexts. This Bajika rendition not only enriches scholarly discourse but also empowers indigenous voices, fostering intellectual pluralism and regional identity.